An Analysis of Personality Traits of Indonesian Start-Up Entrepreneurs Based on Social Media Footprint - Banguning Asgha; Dang Arif Hartono; Metta Suryatie Halim; Katherin Wijaya; Elaine Ngan; Claudy Marciani Surya (School of Business, IPB University (SB-IPB), 2020)
The objective of this research was to analyze the personality traits of successful Indonesian start-up entrepreneurs whose businesses were in the top 200 based on start-upranking.com. Using IBM Watson Personality Insights, the Big Five personality traits from 27 samples were measured. The Big Five personality traits include openness, conscientiousness, extraversion, agreeableness, and neuroticism. The data were analyzed using descriptive statistics and mean comparison. Mann-Whitney U test was used to determine the difference in personalities between genders, while the Spearman test was utilized to identify the correlation between education level and personalities. The results revealed that Indonesian start-up entrepreneurs tended to be more open, more conscientious, moderate in extraversion, less agreeable, and more neurotic (O+, C+, E, A-, N+). There was no personality difference in different genders and no correlation between education level and personality traits either. The results of this study should serve as a point of departure for future studies on start-up entrepreneurs’ personality traits in Indonesia. Additionally, future studies are suggested to employ a larger number of samples from different countries. Keywords: angel investors, big five personality traits, Indonesian entrepreneurs, social media analysis, start-up